PENGARUH JARAK KONDUKTOR BERKAS TERHADAP RUGI DAYA PADA SUTET 275 KV KILIRAN JAO - PAYAKUMBUH - Dawati, Gustinel; Erhaneli, Erhaneli; Bandri, Sepannur; Dewi, Arfita Yuana; Zulkarnaini, Zulkarnaini (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The goal of the research on the effect of beam conductor distance on power losses on the 275 kV Kiliran Jao to Payakumbuh SUTET's 126.4 km long line is to determine the inductive reactance value based on power losses on inductive resistance and reactance rather than distance. The inductive reactance value is not based on the beam conductor distance of XL= 0,3111 km with a total inductive reactance value of Xtotal= 39,323Ω/km , according to the findings of the calculations performed. Based on the beam conductor distances of XR=0.238 km on distance (s)=0.06m, XL=0,3111 Ω/km on phase distance(s) = 0.26m (distance at system),and XL=0,2931 Ω/km on distance (s)=0.46m, the inductance reactance value is calculated. In the meantime, inductive reactance has a value of 34,8 MW in power loss, resistance has a value of 122 MW in power losses and capasitive reactance has a value 31,5MW in power loss. According to the calculation's findings, large currents and resistance can affect the amount of power lost in resistance, whereas the radius of the conductor wire, the spacing between conductors, and the number of layers of conductor wire can affect the amount of power lost in inductive reactance.Keywords : Conducting wire, Inductive reactance value, Power losses